초대형 부유식 구조물의 돌핀-펜더계류시스템에 관한 실험연구 - 김진하(Jin-Ha Kim); 조석규(Seok-Kyu Cho); 홍사영(Sa-Young Hong); 김영식(Young-Shik Kim) (大韓造船學會 論文集, 2005)
in this paper a dolphin-fender moored pontoon-type floating structure in shallow water depth is studied focusing on mooring force. The pontoon-type floating structure is 500m long, 300m wide. The structure has partially non-uniform drafts of 2.0m and 3.0m. The employed mooring system is a guyed frame type dolphin-fender system. The 1/125 scale model fender system is made of rubber tube to have hi-linear load deflection characteristics. A series of model tests has been conducted focusing on motion and fender force responses in regular and irregular waves at KRISO's ocean engineering basin Non-linear numerical simulation of fender reaction force has been carried out and the results are compared with those of model tests. The simulated rigid body motion and mooring forces also have been compared with the test results.